중생 고품질 단간 복합내병성 벼 품종 “풍미 1호” - 박노봉(No-Bong Park); 곽도연(Do-Yeon Kwak); 여운상(Un-Sang Yeo); 이점식(Jeom-Sig Lee); 송유천(You-Chun Song); 장재기(Jae-Ki Chang); 이종희(Jong-Hee Lee); 남민희(Min-Hee Nam); 김명기(Myeong-Ki Kim); 임상종(Sang-Jong Lim); 황흥구(Hung-Goo Hwang); 신문식(Mun-Sik Shin); et al. (Korean journal of breeding, 2009)
"풍미1호"는 영남농업연구소에서 재배안전성이 높은 고품질 벼를 육성하고자 '92/'93년 동계에 단간이면서 내병성이 양호한 YR13616Acp 1을 모본으로 하고 품질이 뛰어난 밀양 122호를 부본으로 인공교배시켜 집단육종법과 계통육종법을 병행 실시하여 YR15675-B-B-B-32-1-2-3 계통을 선발하였다. 생산력검정 시험과 '03~'05년 3개년간 지역적응시험을 실시한 결과 그 우수성이 인정되어 '05년 농작물 직무육성 신품종 선정위원회에서 국가 A newly developed rice variety "Pungmi 1" is a japonica rice(Oryza sativa L.) with high grain quality and multi-resistant to diseases. It was developed by the rice breeding team of Yeongnam Agricultural Research Institute (YARI), RDA. in 2004. This variety derived from a cross between "YR13616Acp 1", having short culm and multi-resistance to biotic stresses and "Milyang 122" with good grain quality. It has short stature of 73cm in culm length and mid-early flowering date of Aug. 13. This variety is moderately resistant to leaf blast showing durable resistance of lower 10% diseased leaf araea in sequential planting meothod. Milled rice kernel of "Pungmi 1" is translucent, clear in chalkness and good at eating quality in panel test. Milling recovery and head rice ratios were comparable to Milyang 122, while it has low protein content. The milled rice yield potential of "Pungmi 1" is about 5.59 MT/ha at ordinary fertilizer level of local adaptability test. This cultivar would be adaptable to Yeongnam inland plains and southern coastal areas of Yeongnam province at ordinary transplanting as well as after barly cultivation.